Negotiation Between Santri Husband and Wife in Fulfilling Rights and Obligations: A Study at Al-Munawwir Islamic Boarding School, Krapyak, Yogyakarta - Muhammad Dzulfikri Yasir; Zakiyuddin Abdul Adhim; Syarif Bahaudin Mudore (Syakhsiyah Jurnal Hukum Keluarga Islam, 2026)
Marriage among santri who continue to live within the pesantren environment presents distinctive challenges in fulfilling spousal rights and obligations, particularly when religious commitments such as Qur’anic memorization remain a priority after marriage. This article aims to examine the forms and mechanisms of negotiation employed by santri couples in fulfilling marital rights and obligations, as well as to analyze the role of the pesantren environment in shaping and constructing marital relations among couples who remain santri at Pondok Pesantren Al-Munawwir Krapyak Yogyakarta. This study employs field research with a case study design and a descriptive-analytical approach, using a normative-sociological framework. Data were collected through direct observation and in-depth interviews with two married santri couples residing in the pesantren, supported by secondary data from Islamic legal sources and relevant scholarly literature. Data analysis was conducted qualitatively using an inductive method within the theoretical framework of Pierre Bourdieu’s concepts of habitus, capital, and field. The findings indicate that santri couples develop distinctive negotiation patterns, including agreements to postpone cohabitation as a consequence of their commitment to Qur’anic memorization, which affects the normative fulfillment of spousal rights and obligations. However, these challenges are mitigated through shared commitment, intensive communication, and mutual understanding. The pesantren environment plays a significant role in shaping the couples’ habitus through the internalization of socio-cultural and religious values, such as acceptance and submission to the process (terimo ing pandum), which sustain marital continuity among santri couples.